Flexible Cobalt-Embedded Carbon Nanosheet/Carbon Nanofiber Composites for Enhanced Electromagnetic Wave Absorption Performance - Wen, Bo; Zhou, Ziyi; Wang, Silan; Zhao, Hongyang; Yang, Guorui; Wang, Jiuhong; Niu, Jiaxi; Miao, Yunzi; Zhang, Zhijie; Yan, Wei; Ding, Shujiang (ACS applied nano materials, 2023)
The rational design of multicomponent materials with tunable microstructures has demonstrated remarkable advantages for attenuating electromagnetic waves (EMWs). Herein, flexible Co-embedded carbon nanosheets/carbon nanofibers (Co@CNSs@CNFs) with three-dimensional structures were prepared by the combination of electrospinning and in situ deposition methods, which demonstrate a high specific surface area (62.2 m2 g–1) and rich interfaces between the cobalt nanoparticle and the carbon matrix confirmed by the investigations of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). As a result, the products achieved a broad effective absorption bandwidth of 5.6 GHz and a strong reflection loss of −76.5 dB with a thin thickness of 2.2 mm. It is found that the affluent electromagnetic wave transmission paths and enhanced interfacial polarization loss are the primary reason for the improvement of the EMW absorption performance. This work proposes a tailored way to fabricate the assembled three-dimensional structure and boost EMW absorption through the synergistic effect of multiple polarization loss mechanisms.